The long-term impact of vaccine clinical research on national stakeholders involved: Experience from a low-income Country - Rejwana Haque Pial; Ganesh Kumar Rai; Rajeev Shrestha; Santa Kumar Das; Ram Hari Chapagain; Shipra Chaudhary; Dipesh Tamrakar; Piush Kanodia; Pragya Thapa; Sridhar Vemula; Birendra Prasad Gupta; Alexandra Hill; et al. (Human Vaccines & Immunotherapeutics)
Clinical trials are the most rigorous scientific and regulated method to investigate the safety and efficacy of vaccines or drugs in pre-licensure stage. Clinical trial design and implementation are complex, time-consuming and involves close engagement with country’s regulatory authority, clinical trial sites, investigators, and the healthcare system. Over the past few decades, a significant number of clinical trials have been conducted in low- and middle-income countries (LMICs), particularly in resource-limited settings. Conducting clinical research in LMICs leads to significant capacity building in terms of training and infrastructure, which adds to the improvement in overall public health benefits of the country. Here, we describe the advances in local capacities, infrastructure and healthcare system following the implementation of clinical trials with the contribution of the International Vaccine Institute at different trial sites in Nepal from 2017 to 2024 in urban, semi-urban, and rural settings. We highlight how, in addition to achieving the study-specific objectives, this experience has built local scientific, ethical, and regulatory oversight capabilities and physical infrastructure. Such positive experiences will provide additional rationale for health research organizations, pharmaceutical companies, and funders to engage in the implementation of further vaccine clinical research with LMICs which bear a heavy burden of infectious diseases.